AN ANALISYS OF SPEAKING INTERACTIVE PROBLEMS OF ELEVENTH GRADE STUDENTS IN HOSPITALITYDEPARTMENT IN SMK 17 AGUSTUS 1945 CLURING - Dea Nurya Hayu; Sutami Dwi Lestari; Arin Inayah (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2022)
Speaking interactive is one type of speaking that has long duration in conversation. This research aimed to find the problem and the problem solving in speaking interactive of student in SMK 17 Agustus 1945 Cluring. The research design was descriptive qualitative. The respondents were 136 which determined by using random sampling. The data were taken by using online system of questionnaire and interview. The data from questionnaire was analysed by using Likert scale. The data analysis was determined based on theory linguistics problem and non-linguistic problem. There are 3 problems in linguistic and there are 5 problems in non-linguistic. Analysis questionnaire and interview data showed that students at SMK 17 Agustus 1945 Cluring have high problem in speaking interactive. The type of speaking interactive problems had by students showed the percentage score of each indicator are 63% in speaking interactive problem, 62% in lack of grammar, 67% lack of vocabulary, 73% lack of pronunciation, 62% in lack of confident, 65% little talking time, 51% in lack of motivation, 61% in lack of listening skill, and 62% in lack of giving feedback. Based on the data result, the problem solving that is suitable in speaking interactive is having interactive conversation through Small Talk, Ome-Tv, and watching YouTube channel continuously in daily life.